Impact of Capital Structure, Loan to Deposit, Firm Size and Asset Tangibility on the Profitability of Nepalese Commercial Banks - Bhandari, Pravisha (Nepalese Journal of Finance, 2024)
This study examines the impact of capital structure, loan to deposit, firm size and asset tangibility on the profitability of Nepalese commercial banks. Return on asset, return on equity and earnings per share are selected as the dependent variables. Similarly, capital adequacy ratio, asset tangibility, firm size, loan to deposit, debt to total assets ratio and debt to total equity ratio are selected as the independent variables. This study is based on secondary data of 13 commercial banks with 104 observations for the study period from 2013/14 to 202/21. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank, annual reports of the selected commercial banks and reports published by Ministry of Finance. The correlation coefficients and regression models are estimated to test the significance and importance of capital structure, loan to deposit, firm size and asset tangibility on the profitability of Nepalese commercial banks. The study showed that debt to equity ratio has a positive impact on return on assets, return on equity and earnings per share. It indicates that increase in debt-to-equity ratio leads to increase in return on assets, return on equity and earnings per share. Similarly, debt to assets ratio has a positive impact on return on assets, return on equity and earnings per share. It indicates that increase in debt to assets ratio leads to increase in return on assets, return on equity and earnings per share. Moreover, capital adequacy ratio has a positive impact on return on assets and return on equity. It indicates that increase in capital adequacy ratio leads to increase in return on assets and return on equity. In addition, firm size has a positive impact on return on assets and return on equity. It indicates that increase in assets size leads to increase in return on assets and return on equity. Furthermore, asset tangibility has a negative positive impact on return on assets, return on equity and earnings per share. It indicates that increase in asset tangibility leads to decrease in return on assets, return on equity and earnings per share. Likewise, loan to deposit ratio has a negative positive impact on return on assets, return on equity and earnings per share. It indicates that increase in loan to deposit ratio leads to decrease in return on assets, return on equity and earnings per share of Nepalese commercial banks.